Interaction of histidine-rich glycoprotein with fibrinogen and fibrin. - Leung, L L (1986)
Histidine-rich glycoprotein (HRGP) is a human plasma and platelet protein of apparently diverse biological functions. In this study a new interaction for HRGP is described. HRGP specifically interacts with fibrinogen as demonstrated by two independent systems. Using an enzyme-linked immunosorbent assay it was demonstrated that HRGP bound to adsorbed fibrinogen in a concentration-dependent and saturable manner, with an apparent dissociation constant (Kd) of 6.7 nM. The binding was specific, reversible, and not mediated by a conformationally altered adsorbed fibrinogen molecule. The interaction was divalent cation-dependent and ionic in nature. The HRGP-fibrinogen interaction was also demonstrated using rocket immunoelectrophoresis. The HRGP-fibrinogen interaction had an effect on the kinetics of conversion of fibrinogen to fibrin as demonstrated by a prolongation of the thrombin time. HRGP also became incorporated into fibrin clots in a concentration-dependent and saturable manner, with an apparent Kd of 0.25 microM. The incorporation of HRGP into fibrin clots occurred in a plasma milieu as demonstrated by the direct incorporation of radiolabeled HRGP into plasma clots and by a significant decrease in serum HRGP levels as compared with plasma levels. HRGP prolonged the lag time phase of fibrin gel formation, and decreased the rate of turbidity rise, as well as the final absorbance of fibrin gels. Since the extent of fibrin polymerization was not influenced by the presence of HRGP, these data suggest that fibrin is distributed over more, but thinner, fibrils in the presence of HRGP. In addition to its potential effect on fibrin polymerization, the HRGP-fibrin interaction may play a role in the cell-cell interactions of platelets and macrophages.